Pelatihan Penulisan Naskah dan Pementasan Drama Berbahasa Arab: Legenda Pulau Kemaro - Muhammad Walidin; Masyhur; Faqihul Anam; Isnaini Rahmawati; Ulil Albab (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
This Community Service Activity is intended to enhance motivation and to improve the four fundamental skills in learning Arabic Language for students of Darussalam Islamic Boarding School in Lampung. In order to achieve this goal, the activity uses the drama method with a lecturing approach, mentoring, rehearsal, and culminates in a performance. The result of this activity is that the selected students who become actors are highly motivated in the learning process (writing, reading, speaking, and listening). The composition of the text of the legend 'Pulau Kemaro' is also easier to perform as it is associated with the cultural context of the legend.